Expression Level of Pro-Apoptotic Genes Determine Disease Severity of HbE/Beta thalassemia - Hassan, Rosline (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2019)
• Hb E/(3-thalassemia is inherited disorders that occur as a result of abnormal synthesis of (3-globin • Co-inheritance of a-globin hemoglobinopathies and increase level of HbF have shown to modulate the presentation of Hb E/~-thalassemia J but not in all patients~ suggesting that other factors may contribute to heterogeneity of the disease. • Hb E/~-thalassemia presented with a wide range of disease severity1 ranging from essentially asymptomatic to a severe transfusiondependent state